2019
DOI: 10.3390/ma12050789
|View full text |Cite
|
Sign up to set email alerts
|

Grain Selection in a High-Efficiency 2D Grain Selector During Casting of Single-Crystal Superalloys

Abstract: Using electron backscattered diffraction techniques (EBSD) and optical microscopy (OM), the grain selection and competitive growth in a new-designed high-efficiency two-dimensional (2D) selector during solidification of Ni-based single-crystal (SX) superalloys have been investigated with emphasis on the geometry of the selector part in this article. It is found that the efficiency of the grain selector depends greatly on the thickness and eccentric distance of the selector part. When the thickness is smaller t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The dendrites participating in the competitive growth in selector channel determine the orientation of the final blade. Previous articles by Zhu et al showed that the starter block with a height between 10 mm and 30 mm can optimize the top <001> orientation within 10 degrees, which can meet the requirements of industrial production [1,22]. To better study the influence of the position of the top grain selection channel on the final orientation, we controlled the angle of the take-off angle of the selected section to 15 • , 30 • , 40 • , 50 • and 60 • , the selector diameter was fixed at an optimized value 3 mm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dendrites participating in the competitive growth in selector channel determine the orientation of the final blade. Previous articles by Zhu et al showed that the starter block with a height between 10 mm and 30 mm can optimize the top <001> orientation within 10 degrees, which can meet the requirements of industrial production [1,22]. To better study the influence of the position of the top grain selection channel on the final orientation, we controlled the angle of the take-off angle of the selected section to 15 • , 30 • , 40 • , 50 • and 60 • , the selector diameter was fixed at an optimized value 3 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Jet engine turbine blades are located in the harsh environment behind the burner and rotate at high speed to extract energy from the high-temperature gas stream. Generally speaking, single-crystal Ni-based superalloy is usually used in the gas turbine to optimize its functions and to perform the roles of energy conservation, emission reduction and environmental protection [1][2][3]. To obtain an excellent performance of superalloys, a lot of research has been carried out.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the seeding method can precisely control the orientation of the SC component, it can also cause the occurrence of casting defects, and the operation of this method is inconvenient in practice. Therefore, the selector method is usually used in industrial applications, but for some high-requirement SC casting, a combination of both methods is applied [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain a single-crystal structure, grain selectors are applied during directional solidification. In the process of SX casting, the grain selector is composed of a starter block and a grain selector [1,2,3]. The starter block optimizes the orientation of grains through competitive growth, and the selector ensures that only a single grain eventually survives.…”
Section: Introductionmentioning
confidence: 99%